A Systematic Literature Review : Antecedents, Concepts and Research Sector of Innovative Work Behavior - Kharima, Kholilah Danarratoe; Yulianti, Praptini; Kusyeni, RD (Majalah Ilmiah Bijak, 2023)
Innovative work behaviour is an important focus in dealing with the digitalization era because there is still a lack of individual adaptation to the different changes that occur. There are currently few research models constructed to see IWB, thus this study seeks to conduct additional research on the most recent concepts in IWB so that it can be carried out in areas where IWB has not yet reached. The antecedents, concepts, and sectors involved in IWB are investigated using a literature review method in this study. Furthermore, a bibliometric technique was employed in this study to obtain a clear picture of the IWB's applicability. The results of this study show that IWB has numerous antecedents that may be categorised into three categories: individual, organisational, and leadership. Related to the concept of IWB is divided into three sets of concepts, namely innovative work behaviour for learning and leadership, innovative work behaviour for process and performance, innovative work behaviour for characteristic and conditions, and for sectors that carry out IWB more in telecommunications and manufacturing, but it is also necessary that in the future IWB can be more widespread in all sectors, especially the public sector which provides public services.